Trichormamides C and D, antiproliferative cyclic lipopeptides from the cultured freshwater cyanobacterium cf. Oscillatoria sp. UIC 10045. Issue 13 (1st July 2015) - Luo, Shangwen; Kang, Hahk-Soo; Krunic, Aleksej; Chen, Wei-Lun; Yang, Jilai; Woodard, John L.; Fuchs, James R.; Hyun Cho, Sang; Franzblau, Scott G.; Swanson, Steven M.; Orjala, Jimmy
Graphical abstract: Abstract: Extract from the cultured freshwater cf. Oscillatoria sp. UIC 10045 showed antiproliferative activity against HT-29 cell line. Bioassay-guided fractionation led to the isolation of two new cyclic lipopeptides, named trichormamides C (1 ) and D (2 ). The planar structures were determined by combined analyses of HRESIMS, Q-TOF ESIMS/MS, and 1D and 2D NMR spectra. The absolute configurations of the amino acid residues were assigned by advanced Marfey's analysis after partial and complete acid hydrolysis. Trichormamides C (1 ) is a cyclic undecapeptide and D (2 ) is a cyclic dodecapeptide, both containing a lipophilic β-aminodecanoic acid residue. Trichormamide C (1 ) displayed antiproliferative activities against HT-29 and MDA-MB-435 cancer cell lines with IC50 values of 1.7 and 1.0 μM, respectively, as well as anti- Mycobacterium tuberculosis activity with MIC value of 23.8 μg/mL (17.3 μM). Trichormamide D (2 ) was found to be less potent against both HT-29 and MDA-MB-435 cancer cell lines with IC50 values of 11.5 and 11.7 μM, respectively.